MODEL OF PREPARATION OF EDUCATORS OF PRESCHOOL EDUCATIONAL ORGANIZATIONS FOR INNOVATIVE ACTIVITIES - Karimova Z.A. (Web of Journals Publishing, 2023)
The article highlights the importance of training pedagogues of the multidisciplinary specialized state preschool education organization in our country for innovative activities, as well as the reforms being carried out in our country in this regard. The requirements for the activities of pedagogues of multidisciplinary pre-school educational organizations are revealed on the example of the qualification description of the position of teacher-defectologist. Also, the content of the model of preparing the editors of preschool educational organizations of the blind sector for innovative activities envisages highlighting the requirements for activities and the customized curriculum for children with special needs aged 2-7 years.
Keywords: Model, inquisitiveness, creativity, discovery, creativity, non-traditional method, information and communication technologies, inclusive education, rehabilitation, child with special needs, state requirements, program.